Developing a UK sarcopenia registry: recruitment and baseline characteristics of the SarcNet pilot. (26th May 2021) - Witham, Miles D; Heslop, Philip; Dodds, Richard M; Clegg, Andrew P; Hope, Suzy V; McDonald, Claire; Smithard, David; Storey, Bryony; Tan, Ai Lyn; Thornhill, Anna; Sayer, Avan A
Abstract: Background: sarcopenia registries are a potential method to meet the challenge of recruitment to sarcopenia trials. We tested the feasibility of setting up a UK sarcopenia registry, the feasibility of recruitment methods and sought to characterise the pilot registry population. Methods: six diverse UK sites took part, with potential participants aged 65 and over approached via mailshots from local primary care practices. Telephone pre-screening using the SARC-F score was followed by in-person screening and baseline visit. Co-morbidities, medications, grip strength, Short Physical Performance Battery, bioimpedance analysis, Geriatric Depression Score, Montreal Cognitive Assessment, Sarcopenia Quality of Life score were performed and permission sought for future recontact. Descriptive statistics for recruitment rates and baseline measures were generated; an embedded randomised trial examined the effect of a University logo on the primary care mailshot on recruitment rates. Results: sixteen practices contributed a total of 3, 508 letters. In total, 428 replies were received (12% response rate); 380 underwent telephone pre-screening of whom 215 (57%) were eligible to attend a screening visit; 150 participants were recruited (40% of those pre-screened) with 147 contributing baseline data. No significant difference was seen in response rates between mailshots with and without the logo (between-group difference 1.1% [95% confidence interval −1.0% to 3.4%], P  = 0.31). The mean age of enrollees was 78 years; 72 (49%) were women. In total, 138/147 (94%) had probable sarcopenia on European Working Group on Sarcopenia 2019 criteria and 145/147 (98%) agreed to be recontacted about future studies. Conclusion: recruitment to a multisite UK sarcopenia registry is feasible, with high levels of consent for recontact.